Morphology in multilingual data resources: A brief survey - Ševčíková, Magda (Estudos Linguísticos (São Paulo. 1978), 2025)
This paper presents selected multilingual language resources that capture various aspects of morphology. Text corpora, dedicated lexical datasets, and typological databases provide insights into inflection, derivation, and, in some cases, the internal structure of words. With continued improvements in coverage, consistency, and compatibility, these resources have the potential to become a solid basis for a realistic understanding of morphological structures across natural languages. Keywords: morphology; typology; segmentation; corpora; databases.